Failed and successful intentional introductions of fish species into 821 Swedish lakes. Issue 5 (May 2016) - Henriksson, Anna; Rydberg, Cecilia; Englund, Göran
Abstract: Introductions of fish into lakes can be viewed as whole system experiments, which can be used to study the principles of community assembly and factors determining the outcome of species invasions. Freshwater fish species have been translocated by humans for centuries in Sweden, and this activity has been documented by national and regional authorities starting at the end of the 19th century. Based on this documentation and additional interviews with local fishermen, we have compiled a data set that includes 1157 intentional introductions of 26 freshwater fish species into 821 Swedish lakes. The data include both successful and failed introductions; where a successful introduction means that the introduced fish species was present in the lake for ≥20 yr or that reproduction was observed earlier than that. The oldest introduction is from 1658 and the latest from 2002. Additionally, the data set includes species composition, water temperature sum, maximum water temperature, lake area, elevation, longitude, and latitude for all lakes. These data have been used to test hypotheses about biotic resistance and invasion success in three papers. We found the presence or absence of specific species predicted invasion success better than the species richness of the lakes. We also found that species with high invasion success tend to make a large contribution to biotic resistance, which will make communities more resistant in the future as they are invaded by additional species.